The effect of internal pipe wall roughness on the accuracy of clamp-on ultrasonic flow meters - Gu,X; Cegla,F (IEEE Transactions on Instrumentation and Measurement, 2019)
Clamp-on transit-time ultrasonic flowmeters (UFMs) suffer from poor accuracy compared with spool-piece UFMs due to uncertainties that result from the in-field installation process. One of the important sources of uncertainties is internal pipe wall roughness which affects the flow profile and also causes significant scattering of ultrasound. This paper purely focuses on the parametric study to quantify the uncertainties (related to internal pipe wall roughness) induced by scattering of ultrasound and it shows that these effects are large even without taking into account the associated flow disturbances. The flowmeter signals for a reference clamp-on flowmeter setup were simulated using 2-D finite element analysis including simplifying assumptions (to simulate the effect of flow) that were deemed appropriate. The validity of the simulations was indirectly verified by carrying out experiments with different separation distances between ultrasonic probes. The error predicted by the simulations and the experimentally observed errors were in good agreement. Then, this simulation method was applied on pipe walls with rough internal surfaces. For ultrasonic waves at 1 MHz, it was found that compared with smooth pipes, pipes with only a moderately rough internal surface (with 0.2-mm rms and 5-mm correlation length) can exhibit systematic errors of 2 in the flow velocity measurement. This demonstrates that pipe internal surface roughness is a very important factor that limits the accuracy of clamp on UFMs.